A meta-analysis of sex differences in neonatal rodent ultrasonic vocalizations and the implication for the preclinical maternal immune activation model - Alison M. Randell; Stephanie Salia; Lucas F. Fowler; Toe Aung; David A. Puts; Ashlyn Swift-Gallant (Biology of Sex Differences)
Abstract As the earliest measure of social communication in rodents, ultrasonic vocalizations (USVs) in response to maternal separation are critical in preclinical research on neurodevelopmental disorders (NDDs). While sex differences in both USV production and behavioral outcomes are reported, many studies overlook sex as a biological variable in preclinical NDD models. We aimed to evaluate sex differences in USV call parameters and determine if USVs are differently impacted based on sex in the preclinical maternal immune activation (MIA) model. Results indicate that sex differences in USVs vary with developmental stage and are more pronounced in MIA offspring. Specifically, developmental stage is a moderator of sex differences in USV call duration, with control females emitting longer calls than males in early development (up to postnatal day [PND] 8), but this pattern reverses after PND8. MIA leads to a reduction in call numbers for females compared to same-sex controls in early development, with a reversal post-PND8. MIA decreased call duration and increased total call duration in males, but unlike females, developmental stage did not influence these differences. In males, MIA effects varied by species, with decreased call numbers in rats but increased call numbers in mice. MIA timing (gestational day ≤ 12.5 vs. > 12.5) did not significantly affect results. Our findings highlight the importance of considering sex, developmental timing, and species in USVs research. We discuss how analyzing USV call types and incorporating sex as a biological variable can enhance our understanding of neonatal ultrasonic communication and its translational value in NDD research.